EMBRYONIC AND LARVAL DEVELOPMENTS OF SCHIZOTHORAX CURVIFRONS MECKEL AS OBSERVED IN THE LABORATORY - Gupta, S S; Subla, B A (Indian Journal of Fisheries, 2011)
Fertilized eggs of Schizothorax cnrvifrons obtained by dry-stripping methodwere reared for studying the early stages in the life history of the species. Rateof fertilization ranged between 79.61 and 84.43%. The larvae released from theegg shells rested at the bottom, nourished by the bulbous sac, exhibiting nofeeding movements. After 10-12 days, the yolk-sacs having disappeared, the larvaestarted to feed. All the important body organs were formed and become functionalafter 30 days of hatching, and at the 45th day~ after hatching the fryalmost took the shape of the adult, attaining a size of 18-20 mm